2022
DOI: 10.1123/jsr.2021-0216
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Reliability of One-Handed Instrument-Assisted Soft Tissue Mobilization Forces During a Simulated Treatment

Abstract: Clinicians utilize instrument-assisted soft tissue mobilization (IASTM) to identify and treat myofascial dysfunction or pathology. Currently, little is known regarding the ability of clinicians to provide similar IASTM forces across treatment sessions. The authors’ purpose was to quantify clinician reliability of force application during a simulated IASTM treatment scenario. Five licensed athletic trainers with previous IASTM training (mean credential experience = 5.2 [4.3] y; median = 5 y) performed 15 one-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Initial efforts to quantify IASTM forces used by trained clinicians have been conducted on simulated tissue attached to a force plate: one-handed IASTM strokes resulted in 2.6 to 14.0 N for peak forces and 1.6 to 10.0 N for average force across clinicians [13], while two-handed IASTM stroke forces ranged from 1.1 to 21.3 N for average peak force and 0.9 to 15.3 N for average mean force across clinicians [14]. Simulated treatment scenarios have also found that trained clinicians can be reliable when applying forces across days when using instruments of different sizes, shapes, and weights [15]. Interestingly, findings from simulated treatment studies have also indicated the potential for different instruments and grip types (i.e., one versus two-handed grips) to impact the amount of force being applied over a single simulated treatment session [14].…”
Section: Introductionmentioning
confidence: 92%
“…Initial efforts to quantify IASTM forces used by trained clinicians have been conducted on simulated tissue attached to a force plate: one-handed IASTM strokes resulted in 2.6 to 14.0 N for peak forces and 1.6 to 10.0 N for average force across clinicians [13], while two-handed IASTM stroke forces ranged from 1.1 to 21.3 N for average peak force and 0.9 to 15.3 N for average mean force across clinicians [14]. Simulated treatment scenarios have also found that trained clinicians can be reliable when applying forces across days when using instruments of different sizes, shapes, and weights [15]. Interestingly, findings from simulated treatment studies have also indicated the potential for different instruments and grip types (i.e., one versus two-handed grips) to impact the amount of force being applied over a single simulated treatment session [14].…”
Section: Introductionmentioning
confidence: 92%
“…Simulated one-handed treatment scenarios on a force plate resulted in applied IASTM forces ranging from 2.6 to 14.0 N for average peak force and 1.6 to 10.0 N for average mean force across clinicians during one-handed IASTM grips 13. Additionally, there is evidence for intraclinician reliability of applied IASTM forces for one-handed IASTM grips with the TG, FAT and RB 14. While IASTM force reliability data for a two-handed grip was not identified in the literature, two-handed force data from a simulated treatment on a force plate was found: IASTM forces ranged from 1.1 to 21.3 N for average peak force and 0.9 to 15.3 N for average mean force across clinicians using the EM, RB, FAT, TG and GT instruments 15.…”
Section: Introductionmentioning
confidence: 93%
“… 13 Additionally, there is evidence for intraclinician reliability of applied IASTM forces for one-handed IASTM grips with the TG, FAT and RB. 14 While IASTM force reliability data for a two-handed grip was not identified in the literature, two-handed force data from a simulated treatment on a force plate was found: IASTM forces ranged from 1.1 to 21.3 N for average peak force and 0.9 to 15.3 N for average mean force across clinicians using the EM, RB, FAT, TG and GT instruments. 15 The variations in the range of forces reported by these studies across the aforementioned instruments requires further investigation into whether grip or instrument influenced force application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach to improve the patient's musculoskeletal dysfunctions, with the help of one or more IASTM, not only improves some functional parameters for the patient but can protect the joints of the operator's/clinician's hand. Recent studies have shown that clinicians who treat myofascial disorders can apply sufficient force to reach the desired tissue depth through the use of IASTM [45,46]. This allows the operator to save the use of the joints of the hand [47].…”
Section: The Significant Advantages Of Using An Iastm In Manual Therapymentioning
confidence: 99%